Influencing factors of preschool teachers’ intention to accept and use mobile learning in early childhood science education: implications on teacher education / Lin Chen, Sharipah Ruzaina Syed Aris and Mohd Khairezan Rahmat - Lin, Chen; Syed Aris, Sharipah Ruzaina; Rahmat, Mohd Khairezan (Universiti Teknologi MARA, 2024)
The adoption and integration of mobile learning technology in early childhood education is a topic of increasing interest and importance. It is crucial to comprehend the factors that affect preschool teachers' intention to accept and use mobile technology. Guided by UTAUT2 as a theoretical lens, the study offered quantitative validation of core technology acceptance factors and their implications. This study investigated 272 preschool teachers in Wuyishan City of Fujian province through SPSS 22 and AMOS 22 data analysis. The results show that performance expectation, effort expectation, social influence, promotion condition, hedonic motivation and habit have significant effects on the behavioral willingness to accept mobile learning. Facilitating conditions and habit support influence usage behavior. Furthermore, learning values do not support behavioral intentions. The findings contribute empirically substantiated and context-specific insights to strengthen the foundations of technology adoption theory while also generating practical guidance to foster mobile learning in Chinese early childhood education.